2020
DOI: 10.3389/fphar.2020.567048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Test Criteria for HLA Genotyping to Prevent Drug Hypersensitivity Reactions: A Systematic Review of Actionable HLA Recommendations in CPIC and DPWG Guidelines

Abstract: Introduction: Certain HLA variants are associated with an increased risk of hypersensitivity reactions to specific drugs. Both the Clinical Pharmacogenetics Implementation Consortium (CPIC) and the Dutch Pharmacogenetics Working Group (DPWG) have issued actionable HLA genedrug interaction guidelines but diagnostic test criteria remain largely unknown. We present an overview of the diagnostic test criteria of the actionable HLAdrug pairs. Methods: A systematic literature search was conducted in PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 92 publications
1
29
0
Order By: Relevance
“…Some studies have reported a close genetic relationship between HLA alleles and drug allergy susceptibility (5,6). These genetic associations may be drug-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported a close genetic relationship between HLA alleles and drug allergy susceptibility (5,6). These genetic associations may be drug-specific.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic associations may be drug-specific. For example, HLA-B*1502 is related to SJS induced by carbamazepine (6), HLA-B*55:01 is related to penicillin allergy (7), and HLA-B*5801 is related to severe skin adverse reactions induced by allopurinol (6).…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic risk scores derived from schizophrenia and depression GWAS have been associated with lithium response [39,40], but none of these findings have been replicated. The immunologic genes HLA-A and HLA-B are robustly linked to rare, but potentially fatal, severe cutaneous adverse reactions (SCARs) (e. g., Stevens-Johnson syndrome [SJS] and toxic epidermal necrolysis [TEN]) following exposure to carbamazepine, oxcarbazepine, and phenytoin [41]. Specifically, HLA-A * 31:01 and HLA-B * 15:02 alleles are associated with a higher risk of SCARs if exposed to carbamazepine [12], while only the HLA-B * 1502 allele is linked to a higher risk of SCARs following exposure to oxcarbazepine and phenytoin [42].…”
Section: Mood Stabilizers/anticonvulsantsmentioning
confidence: 99%
“…A retrospective cohort study 70 The frequency of the HLA-B*5801 allele carriers among Asians is about 10% to 20% but may further vary. 71,72 Testing for HLA-B*5801 among Asians had a high sensitivity (88%-100%) and specificity (82%-94%) in the population with allopurinol-induced severe cutaneous adverse reaction (SCAR) cases. 71 A cohort study (n = 4346) demonstrated that patients who tested positive for HLA-B*5801 and were not prescribed allopurinol had a lower risk of SCAR up to 2 months after ULT initiation compared with those who were not tested but were given allopurinol.…”
Section: Among Adults With Gout Initiating Ult Who Are Intolerant or With Contraindications To Colchicine We Suggest Nsaids As Second-linmentioning
confidence: 99%